MILITARY REFORMS AND ACHIEVEMENTS OF ALAUDDIN KHILJI - Zumeer Ahmad Sofi (CV. Radja Publika, 2023)
Alauddin Khilji, the sovereign of the Delhi Sultanate during the medieval period in India, was confronted with a plethora of martial challenges throughout his rule. Among these challenges were the defence against Mongol incursions, the quelling of internal insurrections, the enlargement of the territorial boundaries of the Sultanate, and the surmounting of various logistical hindrances. In response to these exigencies, Khilji undertook considerable military reforms. These included the formation of a standing army, the enactment of rigorous disciplinary protocols, the initiation of the branding system for horses, and the erection of strategically positioned fortifications. These alterations were instrumental in fortifying his authority, augmenting the territorial expanse of the Sultanate, enhancing the efficacy of the military forces, and reinforcing the stability of the Delhi Sultanate. The military tactics and decisions of Khilji, encompassing his assertive expansionist approach and focus on defence, intelligence acquisition, and utilisation of resources, facilitated his martial triumphs and induced a transformative effect on the socio-political fabric of the Sultanate.